Answer in attachment below.... Open it up in a new window to see it in full.
Answer: -5
Step-by-step explanation: The common difference is the same number we are adding each time to get from one term to the next.
In this sequence, we are adding -5 each time
so our common difference is -5.
Answer:
THE ANWSER IS 4
Step-by-step explanation:
Answer:
2c put me as brainlest
Step-by-step explanation:
Let's solve for c.
b=2c+6
Step 1: Flip the equation.
2c+6=b
Step 2: Add -6 to both sides.
2c+6+−6=b+−6
2c=b−6
Step 3: Divide both sides by 2.
2c
2
=
b−6
2
c=
1
2
b−3
Answer:
c=
1
2
b−3
now if ur just looking for the funtipn the asnwer would be 2c i think